Cardiovascular Characterization of Children and Adolescents with Sickle Cell Anemia - Nancy González Vales; Ximena Laura Graña; Lucía Díaz Morejón; Tamara Sánchez Estrada; Belkis Rodríguez Jorge; Ifraín Machín Caride (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Foundation: sickle cell anemia is a severe chronic hemolytic anemia with a high morbidity and mortality rate. It is well tolerated by the cardiovascular system for a long time, but as years pass, cardiac function is affected. Objective: to determine the cardiovascular disturbances in patients with sickle cell disease. Methods: a descriptive and cross-sectional study was conducted in the hematology and cardiology consultations of the Paquito González Cueto de Cienfuegos University Pediatric Hospital from July 1, 2011 to July 31, 2012. The variables analyzed were: age, sex, mean baseline hemoglobin, nutritional status, interrogation and physical examination, bloo Results: the predominant age group was 7 to 10 years old, with 52.4 %, with a predominance male sex standing out, baseline hemoglobin between 80 and 90.9g / l represented 57 %. 85.7 % had hepatomegaly and in 71.4 % there was arterial dance, 57.1 % showed systolic murmur and 23.8 % suprasternal beat. 100 % of the cases presented normal electrocardiogram and echocardiogram. The correlation between baseline hemoglobin and nutritional status showed a prevalence of 66.7 % for eutrophic children, with SB thalassemia predominating with 80 %. 57 % presented cardiovascular repercussion mainly the group of 7 to 10 years with 63.6 %. Conclusions: it was possible to identify cardiovascular disturbances through clinic features and a slight impact was observed, confirmed only by the telecardiogram, where the presence of grade l-ll cardiomegaly was identified.